East Java Tobacco Competitiveness in the International Market - Winadinata Grace Angelina Wijaya; Sri Widayanti; Nisa Hafi Idhoh Fitriana (MediaTrend, 2023)
Tobacco production in East Java Province experienced various problems that caused the export performance of East Java Province tobacco to fluctuate in the international market. This study aims to analyze the comparative and competitive competitiveness of East Java Province tobacco exports in the international market from 2007 to 2021. The analytical method used in this study is Revealed Comparative Advantage (RCA) to analyze comparative competitiveness and the Trade Specialization Index (TSI) or Trade Specialty Index (ISP) to analyze competitive advantage. Based on the results of the RCA analysis, it shows that East Java Province's tobacco exports in the international market have strong comparative competitiveness because the RCA value is greater than 1, with an average value of 16.31. ISP analysis results are less than 0 to 1 or negative, with an average value of -0.26. The ISP value of East Java tobacco exports indicates that East Java Province tends to be an importer rather than an exporter and is in the import substitution stage. The need for large consumption should be met by domestic production to reduce tobacco imports due to the high comparative competitiveness of East Java tobacco in the international market.